Significance of Bioceramics for Bone Surgery - Ślósarczyk, A. (Engineering Transactions, 2001)
The paper presents ceramic implant materials used in orthopaedics, restorative dentistry, maxillofacial surgery and otholaryngology. In addition to oxide ceramics, also materials on the basis of calcium phosphates are presented, including composites with hydroxiapatite or TCP matrix. Possible types of behaviour of implantation materials and living tissues as well as resulting classification of biomaterials, subdivided into: nearly inert, bioactive and resorbable, are discussed. Attention was drawn to the most prospective directions of research studies of biomaterials for the future.